Nonpoint source pollution: experiments on the average Pigouvian tax under costly communication. (25th September 2018) - Sarr, H; Bchir, M A; Cochard, F; Rozan, A
Abstract: The 'average Pigouvian tax' (APT) was proposed to reduce the financial burden imposed by the standard ambient tax. This instrument consists of a standard ambient tax divided by the number of firms and it requires polluters to cooperate in order to achieve the social optimum. To enable polluters to cooperate, communication is allowed in most of the experimental treatments. We introduce different types of communication: cheap talk, exogenous costly communication and endogenous costly communication. Our experiment confirms that under cheap talk, the APT promotes a reduction in polluters' emissions. In contrast, under costly communication, the APT reduces group emissions to a lesser extent.